Climate change impact on the PAH photodegradation in soils: Characterization and metabolites identification. (April 2016) - Marquès, Montse; Mari, Montse; Audí-Miró, Carme; Sierra, Jordi; Soler, Albert; Nadal, Martí; Domingo, José L.
Abstract: Polycyclic aromatic hydrocarbons (PAHs) are airborne pollutants that are deposited on soils. As climate change is already altering temperature and solar radiation, the global warming is suggested to impact the environmental fate of PAHs. This study was aimed at evaluating the effect of climate change on the PAH photodegradation in soils. Samples of Mediterranean soils were subjected to different temperature and light radiation conditions in a climate chamber. Two climate scenarios were considered according to IPCC projections: 1) a base (B) scenario, being temperature and light intensity 20 °C and 9.6 W/m 2, respectively, and 2) a climate change (CC) scenario, working at 24 °C and 24 W/m 2, respectively. As expected, low molecular weight PAHs were rapidly volatilized when increasing both temperature and light intensity. In contrast, medium and high molecular weight PAHs presented different photodegradation rates in soils with different texture, which was likely related to the amount of photocatalysts contained in both soils. In turn, the hydrogen isotopic composition of some of the PAHs under study was also investigated to verify any degradation process. Hydrogen isotopes confirmed that benzo( a )pyrene is degraded in both B and CC scenarios, not only under light but also in the darkness, revealing unknown degradation processes occurring when light is lacking. Potential generation pathways of PAH photodegradation by-products were also suggested, being a higher number of metabolites formed in the CC scenario. Consequently, in a more or less near future, although humans might be less exposed to PAHs, they could be exposed to new metabolites of these pollutants, which might be even more toxic. Highlights: Low molecular weight PAHs are quickly volatilized in a climate change scenario. PAH photodegradation is highly related to the amount of photocatalysts in soil. Climate conditions do not affect photodegradation of PAHs in fine-textured soil. In the future, people might be exposed to new potentially toxic PAH metabolites. Hydrogen isotopes confirmed benzo(a)pyrene degradation in all climate scenarios.